Digital Literacy and Islamic Spiritual Values as Catalysts for Green Economic Behavior in the Digital Era - Yuliantina, Devi; Ainun, Ainun Jariah; Rahmita Sari; Refa Asmianur; Nafa Aqla Islami (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
This study examines the influence of digital literacy and Islamic spiritual principles on green economic behavior in the context of the digital age. This study identifies a gap in previous studies, which rarely combine technological proficiency and spiritual ethics in influencing sustainable economic behavior among the younger generation. A quantitative approach was used to collect data through questionnaires distributed to Generation Z participants in Palangka Raya City. This study examined three variables, namely digital literacy, Islamic spiritual values, and green economic behavior. Data analysis was conducted using Structural Equation Modeling (SEM) to examine the relationship between variables. The results indicate that digital literacy and Islamic spiritual values significantly and positively influence green economic behavior. Digital literacy increases awareness and encourages responsible decision-making regarding the environment, while Islamic spiritual values strengthen moral and ethical motivation towards sustainability. These findings emphasize the importance of combining digital competence and Islamic spirituality in promoting sustainable economic transformation. This study contributes to the development of green economics literature by providing empirical evidence of the relationship between digital and spiritual factors in shaping sustainable behavior.